Frequency Responses to Visual Tracking Stimuli May Be Affected by Concussion - Maruta, Jun; Jaw, Eugene; Modera, Peter; Rajashekar, Umesh; Spielman, Lisa A.; Ghajar, Jamshid (Military medicine, 2017)
Human visual tracking performance is known to be reduced with an increase of the target's speed and oscillation frequency, but changes in brain states following a concussion may alter these frequency responses. The goal of this study was to characterize and compare frequency-dependent smooth pursuit velocity degradation in normal subjects and patients who had chronic postconcussion symptoms, and also examine cases of acutely concussed patients. Eye movements were recorded while subjects tracked a target that moved along a circular trajectory of 10° radius at 0.33, 0.40, or 0.67 Hz. Performance was characterized by the gain of smooth pursuit velocity, with reduced gain indicating reduced performance. The difference between normal and chronic patient groups in the pattern of decrease in the gain of horizontal smooth pursuit velocity as a function of the stimulus frequency reflected patients performing more poorly than normal subjects at 0.4 Hz while both groups performing similarly at 0.33 or 0.67 Hz. The performance of acute patients may represent yet another type of frequency response. The findings suggest that there may be ranges of stimulus frequencies that differentiate the effects of concussion from normal individuals.